2012
DOI: 10.1097/yic.0b013e328356acad
|View full text |Cite
|
Sign up to set email alerts
|

Paliperidone ER versus risperidone for neurocognitive function in patients with schizophrenia

Abstract: This study aims to determine the effectiveness of paliperidone extended release (ER) on cognitive function in patients with schizophrenia in comparison with risperidone. This was a 12-week, randomized, open-label study on schizophrenia patients who were receiving risperidone. The patients were randomized to a risperidone-continuation group or a paliperidone-switch group. The primary outcome measure was neurocognitive function, which was measured using a computerized battery. Secondary efficacy measures include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 24 publications
2
15
1
Order By: Relevance
“…In particular, motivation is one of a number of important factors that mediate improvement of social functioning [34]. Consistently, Kim et al [35] reported that there was significant improvement in social functioning in the oral PAL group compared to the oral RIS group. In the present study, the different α 2 -adrenergic receptor affinity between RLAI and PP is emphasized because of the peculiarity of RLAI pharmacokinetics.…”
Section: Discussionsupporting
confidence: 53%
“…In particular, motivation is one of a number of important factors that mediate improvement of social functioning [34]. Consistently, Kim et al [35] reported that there was significant improvement in social functioning in the oral PAL group compared to the oral RIS group. In the present study, the different α 2 -adrenergic receptor affinity between RLAI and PP is emphasized because of the peculiarity of RLAI pharmacokinetics.…”
Section: Discussionsupporting
confidence: 53%
“…As paliperidone is the major active metabolite of risperidone, the mechanism of PRL elevation for paliperidone is likely similar to that of risperidone [260262]. However, two recently published studies suggest that PRL levels seem to decrease after switching from risperidone to paliperidone in patients with a psychotic disorder [263, 264].…”
Section: Prl and Antipsychoticsmentioning
confidence: 99%
“…Therefore improvement cannot reliably be attributed to medication effects. In addition, Kim et al (31) found that compared to patients using risperidone, verbal memory improved more in patients using paliperidone extend release (ER), an active metabolite of risperidone with an extended delivery system that decreases fluctuations in serum drug concentrations.…”
Section: Verbal Learning and Memorymentioning
confidence: 99%